The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/jac/dkq470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of carbapenems against a metallo- -lactamase-producing Escherichia coli clinical isolate in a rabbit intra-abdominal abscess model

Abstract: In the rabbit experimental model, carbapenems were shown to be effective in the treatment of intra-abdominal infection due to an extended-spectrum β-lactamase-negative carbapenem-susceptible VIM-1-producing clinical E. coli strain, but treatment with aztreonam resulted in a more favourable outcome overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…Carbapenems and aztreonam were shown to be effective in the treatment of this infection with regard to reductions in bacterial densities and mortality of the animals compared with those of untreated controls. Aztreonam, however, resulted in a more favorable outcome overall than that seen with carbapenems (239).…”
Section: Experimental Infection Modelsmentioning
confidence: 81%
“…Carbapenems and aztreonam were shown to be effective in the treatment of this infection with regard to reductions in bacterial densities and mortality of the animals compared with those of untreated controls. Aztreonam, however, resulted in a more favorable outcome overall than that seen with carbapenems (239).…”
Section: Experimental Infection Modelsmentioning
confidence: 81%
“…Indeed, in studies of carbapenems and aztreonam in animal models of infection due to an MBL-producing (ESBL-negative) Enterobacteriaceae clinical isolate (6), treatment with aztreonam significantly reduced mortality (28).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies provided evidence that carbapenems might have an effect on carbapenemase-producing Enterobacteriaceae (7,13,43). Additionally, it has been recently shown by in vitro time-kill assay that meropenem at concentrations 4ϫ the MIC was bactericidal (Ͼ3 log 10 reduction CFU/ml) even when tested alone against various strains of Klebsiella pneumoniae carbapenemase (KPC)-producing Enterobacteriaceae with an MIC of 2 to 4 mg/liter (38).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it has also been suggested that trough levels severalfold above the MIC could be useful for carbapenems in some settings (23,44,45) and that this approach could be worthwhile even against low-MIC carbapenemase producers (6,7,13,38,43).…”
mentioning
confidence: 99%